SYNTHESIS OF DEUTERIUM-LABELED 5-ALPHA-ANDROSTANE-3-ALPHA,17-BETA-DIOL AND ITS 17-BETA-GLUCURONIDE - CHUNG, BC; MALLAMO, JP; JUNIEWICZ, PE; SHACKLETON, CHL (BUTTERWORTH-HEINEMANN, 1992)
Using unlabeled androsterone as starting material, 5alpha-[16,16-H-2(2)]androstan-3alpha-ol-17-one was synthesized by exchange using deuterated potassium methoxide. This labeled androsterone product was reduced by sodium borodeuteride, which gave predominantly trideuterated 5alpha-androstane-3alpha, 17beta-diol. The labeled androstanediol was conjugated with glucuronide by using the Koenig-Knorr reaction with methyl-1-bromo-1-deoxy-2,3,4-tri-O-acetyl-alpha-D-glucopyranosuronate. The dominant product was identified by thermospray high-performance liquid chromatography/mass spectrometry (MS) and electrospray MS as 5alpha-[16,16,17-H-2(3)]androstane-3alpha, 17beta-diol, 17beta-glucuronide.
Keywords: ANDROSTANEDIOL GLUCURONIDE; IDIOPATHIC HIRSUTISM; PLASMA; WOMEN; CLEARANCE; RATES